Better Pen-and-Paper Surveys for Transportation Research in Developing Countries: A Modified, Stated Preference, Pivoting Approach. Issue 1 (January 2014) - Campbell, Andrew A.; Cherry, Christopher; Ryerson, Megan; Jones, Luke
In developing countries, the rapid pace of socioeconomic and technological change necessitates the use of quick-response survey methods. Transportation researchers often work with limited budgets in environments with relatively low rates of computer and Internet access. Such conditions can preclude the use of the computer-assisted survey methods that are preferred for conducting research in industrialized countries. This paper describes novel methods for low-cost and high-quality data collection in a data-poor environment. The context is a stated preference (SP) experiment to estimate adoption of bikeshare and electric bikeshare in Beijing, but the methods are transferable. Two main methodological contributions are described. The first is a unique survey design that allows SP pivoting to occur within a single pen-and-paper interview (PAPI). For small- to medium-sized surveys, this design is often more cost-effective than traditional pivoting methods that require either a multistage PAPI survey or computer-assisted interviews. The second contribution is the demonstration of the use of affordable GPS technologies and publicly available data for the purpose of survey protocol enforcement and quality control. The paper describes survey design features that are of particular value for nonmotorized or semimotorized transportation research.